2021
DOI: 10.1021/acs.jpcc.1c01179
|View full text |Cite
|
Sign up to set email alerts
|

Strain-Engineered Rippling and Manipulation of Single-Layer WS2 by Atomic Force Microscopy

Abstract: Surface ripple, as an important factor of corrugations in two-dimensional (2D) atomic crystals, plays important roles in determining their mechanical and physical properties. Here, we systematically investigated the strain-engineered rippling structure and manipulation of the rippling domain in monolayer WS2 flakes via atomic force microscopy (AFM). The rippling structure was introduced by the in-plane compression applied through the underlying SiO2/Si substrate during the rapid cooling process of post-growth.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 39 publications
0
25
0
Order By: Relevance
“…Specifically, it is about 7 mV higher in the S-terminated region (Figure f). It is a direct evidence that the S-terminated region weakly adheres to the substrate as compared with the W-terminated region. , …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, it is about 7 mV higher in the S-terminated region (Figure f). It is a direct evidence that the S-terminated region weakly adheres to the substrate as compared with the W-terminated region. , …”
Section: Resultsmentioning
confidence: 99%
“…It is a direct evidence that the S-terminated region weakly adheres to the substrate as compared with the W-terminated region. 23,35 To further confirm the uneven strain distribution in adjacent regions in WS 2 , we transferred the as-grown h-WS 2 from the initial silicon substrate onto a fresh SiO 2 /Si substrate and imaged the PL map under the same experimental conditions. The monolayer h-WS 2 was transferred using a poly(methyl methacrylate) (PMMA)-assisted method, and there is no thermal heating process during the transfer to avoid any additional strain.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Measuring by contact mode AFM the contaminated vdW surfaces reveals a domain structure in the torsion (friction) signal, which cannot be linked to the features in the topography channel and is also present in atomically smooth regions (see FigS3 and FigS8b-c). The origin of these frictional domains [12][13][14][18][19][20][21][22][23] was not conclusively clari ed to date, which hinders the possibility to willingly manipulate or remove them. Our ndings establish a direct causal link between the self-organized stripes of the adsorbed alkane layer and the friction anisotropy (Fig4a-b).…”
Section: Anisotropic Friction Domainsmentioning
confidence: 99%
“…Gallagher et al 13 proposed that a contamination layer could be the cause for the widely reported anisotropic friction on graphene and hBN, but the nature of the molecules forming the ordered surface cover could not be determined. Many groups reported anisotropic friction domains on various vdW materials: monolayer to few layer graphene 13,14,18−21 , hexagonal boron nitride (hBN) 13 , molybdenum disul de (MoS 2 ) 12,21,22 and tungsten disul de (WS 2 ) 23 . In all these reports, the friction anisotropy exhibits common properties, such as a domain structure, C2 rotation symmetry in each domain, 60° angles between the symmetry axes of adjacent domains, despite the differences in the chemical or mechanical properties of the host surface.…”
Section: Introductionmentioning
confidence: 99%